2016
DOI: 10.1515/helmin-2015-0068
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterization of Xiphinema species from Shenzhen, China

Abstract: Summary During a nematode biodiversity survey from 2012 to 2014 in Shenzhen, China, ten nematode populations (SZX1301–SZX1310) of Xiphinema were recovered from rhizosphere of different plants, namely Acacia mangium (SZX1306), A. confuse (SZX1309), Blechnum orientale (SZX1301, SZX1302, SZX1307, SZX1308), Litchi chinensis (SZX1304, SZX1310) in Tianxinshan and Gleichenia linearis (SZX1303, SZX1305) in Yangmeikeng environmental monitoring sites. Morphological and molecular profiles of these populations were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Morphospecies group 1 species are mainly distributed in Brazil (Oliveira et al, 2003;Silva et al, 2008;De Jesus et al, 2015), China (Zeng et al, 2016), USA, Canada (Ye, 2002;Yu et al, 2010), Malaysia (Rahman-Razak and Loof, 1998), France (Luc and Coomans, 1992) and India (Loof et al, 2001). This new species is described from the ornamental plants imported from Japan, which represents the first group 1 species from this country.…”
Section: Discussionmentioning
confidence: 99%
“…Morphospecies group 1 species are mainly distributed in Brazil (Oliveira et al, 2003;Silva et al, 2008;De Jesus et al, 2015), China (Zeng et al, 2016), USA, Canada (Ye, 2002;Yu et al, 2010), Malaysia (Rahman-Razak and Loof, 1998), France (Luc and Coomans, 1992) and India (Loof et al, 2001). This new species is described from the ornamental plants imported from Japan, which represents the first group 1 species from this country.…”
Section: Discussionmentioning
confidence: 99%
“…The South African population are similar to X. peruvianum but are distinguished by their shorter odontostyle and tail shape. This nematode species has been reported in association with a wide range of cultivated plants from Nigeria, Kenya, Iran, Pakistan, Brazil, and Taiwan (Lamberti and Bleve-Zacheo 1979; Bos and Loof 1983; Coomans and Heyns 1997; Fadaei et al 2003; Oliveira et al 2003; Chen et al 2005). Our record of X. oxycaudatum , in association with Cyclopia spp.…”
Section: Discussionmentioning
confidence: 90%
“…The polymerase chain reaction (PCR) to confirm the identity of the nematode specie was carried out by the amplification of the internal transcribed spacer (ITS) region, the D2D3 expansion segment of the 28S gene of the ribosomal DNA, and the portion of the cytochrome oxidase ( coxI ) gene of the mitochondrial DNA. PCR of the ITS region was carried out as described by Chen et al 2005 using KAPA2G 40 Robust HotStart ReadyMix (KAPA Biosystems) with the primer combination of S-ITS1 (5'-TTGATTACGTCCCTGCCCTTT-3') and 28S (5'-TTTCACTCGCCGTTACTAAGG-3'). Amplification was carried out in a thermal cycler with the following cycling condition; 1 cycle at 94 °C for 4 min, followed by 30 cycles at 94 °C for 30 sec, 52 °C for 30 sec, and 72 °C for 2 min 30 sec, and ending with one cycle at 72 °C for 7 min and finally kept at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…X. diffusum are very similar which distinguished by only minute morphological differences ( Brown & Halbrendt, 1997 ). The previous molecular study revealed that X. diffusum and X. brevicolle are close to each other ( Sakai et al, 2011 ; Zeng et al, 2016 ). The result of the present study indicated that X. diffusum grouped with X. brevicolle .…”
Section: Discussionmentioning
confidence: 93%